Modeling of discrete fracmemristor and its application - S. He; K. Sun; Y. Peng; L. Wang (AIP Advances, 2020)
Researches on the fracmemristor have aroused increasing interest in the last several years, but there are no reports on design of the discrete fracmemristor. Based on the fractional-order difference and the mathematical model of the charge-controlled memristor, the discrete fracmemristor is designed where the amount of charge is determined by a fractional-order discrete system. In the numerical simulations, it shows that the pinched hysteresis loops are observed, which imply that the proposed memristor satisfies the definition of the memristor. As an application, the fracmemristor sine map is designed, and multistability is observed regarding the initial conditions of both the memristor and system. It provides a potential model for different applications such as cellular neural networks, modulators, sensors, chaotic systems, and programmable digital circuits.